Regional Economic Outlook, May 2010, Middle East and Central Asia. (Regional Economic Outlook, 2010)
The May 2010 Regional Economic Outlook: Middle East and Central Asia reports on the implications for the region of global economic developments and presents key policy challenges and recommendations. A resumption of capital inflows and the rebound in crude oil prices have aided the recovery in the oil-exporting countries of the Middle East and North Africa. The group of oil-importing countries is expected to show marginal increase in growth in response to a pickup in trade, investment, and bank credit. A key challenge for these countries is to enhance competitiveness to raise growth rates and generate employment. In the Caucasus and Central Asia, exports have begun to pick up, the decline in remittances appears to be slowing or reversing, and capital inflows have turned positive. For 2010, a recovery across the region is projected as the global economy, and in particular Russia, picks up speed. Overall, prospects for the region are improving and the regional impact of the Dubai crisis and events in Greece has been limited so far. Nevertheless, a repricing of sovereign debt cannot be excluded, adding a degree of uncertainty to the outlook.